Late Reactivation of SARS-CoV-2: A Case Report - Coppola, Antonietta; Annunziata, Anna; Carannante, Novella; Di Spirito, Valentina; Fiorentino, Giuseppe (Frontiers in Medicine, 2020)
SARS-CoV-2 is a betacoronavirus that belongs to the family Coronaviridae and the order Nidovirales (1). On December 2019, a series of pneumonia cases caused by a SARS-CoV-2 outbreak was identified in Wuhan, Hubei, China and rapidly spread across the world. The spectrum of SARS-CoV-2 disease (COVID 19) varies from asymptomatic or paucisymptomatic forms to clinical conditions characterised by respiratory failure that necessitate mechanical ventilation and support in an intensive care unit (ICU), and multiorgan and systemic manifestations, in terms of sepsis, septic shock and multiple organ dysfunction syndromes (MODS) (2). Whilst many reports have characterised the clinical, epidemiological, laboratory and radiological features, as well as treatment and clinical outcomes of patients with COVID-19 pneumonia, information on SARS-CoV-2 reactivation remains unreported. Curative and eradicative therapy for COVID-19 is not currently available (3). We report a case of a patient with PCR-confirmed COVID-19 pneumonia, who experienced reactivation after 43 days and negative PCR sampling